(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
Lateritic soil is a prospective source of metals termed critical or strategic metals due to their use in high-technology industries. Critical metals include rare earth elements (REEs). In this study, two profiles of lateritic outcrops from the Ni-producing area of Southeast Sulawesi in Indonesia were sampled for magnetic susceptibility as well µ-XRF analyses to identify how the concentration of critical metals changed during pedogenesis. The results show that there are three different patterns from the bottom layer up. The first pattern is enrichment experienced by Sc, La, Cr, and Ti. The second pattern is depletion experienced by Ni, Nd, and Ho. The third pattern is the localization of high concentration at a certain depth, as experienced by Co, Ce, and V. The concentration of certain critical metals correlates either positively or negatively with magnetic susceptibility, inferring that magnetic susceptibility might be used as a proxy indicator for critical metal concentration in lateritic soil.